2017
DOI: 10.4236/jcc.2017.56002
|View full text |Cite
|
Sign up to set email alerts
|

Data Combination over Physical Layer Using Network Coding with PUM Turbo Codes

Abstract: The Base Station (BS) or access point is the building block of wireless networks, so, we propose exploiting it together with the Network Coding (NC) principle. NC suffers from the complexity of the decoding processes, i.e., complicated Jordan Gaussian Elimination (JGE) processes. So, this paper proposes a deterministic NC algorithm to reduce the number of sequential network decoding steps, and hence minimizing the complexity of JGE process resulting to better time delay and processing time. We propose an algor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 14 publications
0
5
0
Order By: Relevance
“…The future work will be directed to more specific protocols that practically improves the performance of specific applications such as condensed mobile network, intensive wireless sensor network, and other applications such as [19].…”
Section: Discussionmentioning
confidence: 99%
“…The future work will be directed to more specific protocols that practically improves the performance of specific applications such as condensed mobile network, intensive wireless sensor network, and other applications such as [19].…”
Section: Discussionmentioning
confidence: 99%
“…Judiciously linear error correction codes were introduced in [19] as a novel idea to improve physical layer communication reliability, however [19] neither introduced the principle of soft-decoding in the middle nodes, nor applied CoNC at the first stage. More work was performed on PUMTC, such as the work in both [20,21], where in [20] a comprehensive theoretical background for using CoNC on wireless network physical-layer is introduced, and in [21] PUMTC was presented to combine data on the physical layer where the cooperation starts after the first stage in a hard-decision decoding manner. The most recent work for the application of CoNC on the physical layer has been presented in [22], where soft and hard decision encoder-decoder PUMTC was used to show the advantages of performance of the softdecision encoder-decoder over the hard-decision, on a cluster of Wireless Sensor Networks (WSNs).…”
Section: Block Code Pum Code Um Codementioning
confidence: 99%
“…This problem is a special case of the multi-path routing problem considered in the literature [7][8][9][10][11][12][13][14][15][16][17]. The algorithm for solving such a generalized problem has a large computational complexity and the time of solution of such a problem cannot meet the requirements for the means of multipath routing.…”
Section: Optimization Of Traffic Distributionmentioning
confidence: 99%
“…It is shown in [12] that in the general case the linear programming problem is NPcomplete. However, in [11][12][13][14][15][16][17] it is shown that when solving applied problems, such as finding the maximum flow, etc., the simplex method has a polynomial complexity. The computational efficiency of the simplex method according to [11] can be estimated using the following two parameters: number of iterations (admissible basic solutions needed to achieve the optimal solution of the problem) and the total machine time required to solve the problem.…”
Section: N Omentioning
confidence: 99%
See 1 more Smart Citation